Endoscopic resection of large subepithelial esophageal lesions via submucosal tunneling endoscopic resection and endoscopic submucosal dissection: a single-center, retrospective cohort study. (4th May 2022) - Yang, Bin; Han, Huazhong; Shen, Jianhong; Lu, Pinxiang; Jiang, Fei
Abstract: Background: This study aimed to compare the clinical outcomes between submucosal tunneling endoscopic resection (STER) and endoscopic submucosal dissection (ESD) for large subepithelial esophageal lesions (SELs) and analyze risk factors for perforation and piecemeal resection. Methods: The clinicopathological features and outcomes of endoscopic treatment of 56 patients with SELs with diameters ≥30 mm, diagnosed between June 2017 and December 2020, were reviewed in this retrospective cohort study. Patients were divided into two groups (ESD group and STER group). Results: The complete resection rates of the STER and ESD groups were 88.1% and 78.6%, respectively ( p = .398). The operation time of STER was longer than ESD ( p = .03), while the hospital stay of STER was shorter than ESD ( p = .02). The rate of major adverse events associated with ESD was considerably higher than STER group ( p = .035). The extraluminal growth pattern was a risk factor for piecemeal resection, and ESD was an independent risk factor for perforation. Regarding tumors with extraluminal growth patterns, the ESD group's perforation rate was significantly higher than the STER group ( p = .009). There were no recurrence or metastases found during a mean follow-up of 24.4 months. Conclusion: The STER technique has advantages of shorter hospital stays and fewer major adverse events than ESD. The extraluminal growth pattern seems to be a risk factor for piecemeal resection in both ESD and STER. STER appears to be a preferable choice for large SELs with extraluminal growth patterns.